Type III Secretion System of Beneficial Rhizobacteria Pseudomonas simiae WCS417 and Pseudomonas defensor WCS374 - Stringlis, Ioannis A.; Zamioudis, Christos; Berendsen, Roeland L.; Bakker, Peter A. H. M.; Pieterse, Corné M. J. (Frontiers in Microbiology, 2019)
Plants roots host myriads of microbes, some of which enhance the defense potential of plants by activating a broad-spectrum immune response in leaves, known as induced systemic resistance (ISR). Nevertheless, establishment of this mutualistic interaction requires active suppression of local root immune responses to allow successful colonization. To facilitate host colonization, phytopathogenic bacteria secrete immune-suppressive effectors into host cells via the type III secretion system (T3SS). Previously, we searched the genomes of the ISR-inducing rhizobacteria Pseudomonas simiae WCS417 and Pseudomonas defensor WCS374 for the presence of a T3SS and identified the components for a T3SS in the genomes of WCS417 and WCS374. By performing a phylogenetic and gene cluster alignment analysis we show that the T3SS of WCS417 and WCS374 are grouped in a clade that is enriched for beneficial rhizobacteria. We also found sequences of putative novel effectors in their genomes, which may facilitate future research on the role of T3SS effectors in plant-beneficial microbe interactions in the rhizosphere.